Tantangan Multikulturalisme dalam Berbagai Aspek di Indonesia - Husaini, Aldi Al; Rosyada, Ita; Wahab, Juliani Abd; Nurhayati, Nurhayati; Afifah, Mutiara Nur (YASIN, 2022)
Multiculturalism is an understanding or ideology that highly upholds, recognizes differences. The existence of multiculturalism is expected not only to be recognized but also to accept the differences in it both ethnicity, race, religion, between groups and ethnicities, thus requiring the people who live in it to be able to understand these differences and can live side by side properly. The author raised this title with the aim of providing an overview and solution to the conflicts that will be faced in the future. The method in this research is to use literature study, namely by using several references from journals and books so that it can assist the author in completing this discussion.